2009
DOI: 10.1093/annonc/mdn538
|View full text |Cite
|
Sign up to set email alerts
|

Expression of molecular markers in mediastinal nodes from resected stage I non-small-cell lung cancer (NSCLC): prognostic impact and potential role as markers of occult micrometastases

Abstract: Quantitative real-time RT-PCR of CEACAM5 and PLUNC can estimate the presence of micrometastatic cells in LNs with greater precision than current staging method used for assessing tumor recurrence risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In contrast, Rena et al and Goldstein et al and our own laboratory did not corroborate these findings using IHC for AE1/AE3, CK and Cam 5.2 [10,11,14]. Several molecular methods such as nested polymerase chain reaction (PCR) for p53 and K-ras and reverse transcriptase-polymerase chain reaction (RT-PCR) for CEA, CK7, CK19 and MUC1 have also been used for the detection of micrometastases in lymph nodes [12,17,20,24,25]. For example Nosotti et al and Hashimoto et al proposed that the presence of occult metastatic deposits in the hilar and mediastinal lymph nodes detected by RT-PCR for CEA mRNA and mutant allele specific amplification using K-ras or p53 respectively is associated with poor prognosis in patients with NSCLC [17,24].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, Rena et al and Goldstein et al and our own laboratory did not corroborate these findings using IHC for AE1/AE3, CK and Cam 5.2 [10,11,14]. Several molecular methods such as nested polymerase chain reaction (PCR) for p53 and K-ras and reverse transcriptase-polymerase chain reaction (RT-PCR) for CEA, CK7, CK19 and MUC1 have also been used for the detection of micrometastases in lymph nodes [12,17,20,24,25]. For example Nosotti et al and Hashimoto et al proposed that the presence of occult metastatic deposits in the hilar and mediastinal lymph nodes detected by RT-PCR for CEA mRNA and mutant allele specific amplification using K-ras or p53 respectively is associated with poor prognosis in patients with NSCLC [17,24].…”
Section: Introductionmentioning
confidence: 79%
“…As the evaluation of small metastases with IHC or molecular tests is costly and time consuming, all studies have evaluated only a relatively small number of cases collected retrospectively or, as most of our cases, prospectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Perhaps owing to a variety of factors that can influence the results of observational studies, such as sample size, patient selection bias, length of follow-up, treatment effect, and other variables, some studies have reported significant associations between the presence of small nodal metastases and poor prognosis, whereas others did not find such a correlation .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, BPIFA1 detection likely represents respiratory epithelial-derived metastatic cells. In non-small cell carcinoma, BPIFA1-positive lymph nodes were associated with decreased survival, highlighting a potential role for BPIFA1 as a clinical biomarker that affects tumor staging and survival (83,84). It is unclear if expression of BPIFA1 in some epithelial-derived malignancies drives metastases or leads to more aggressive/resistant disease.…”
Section: Malignanciesmentioning
confidence: 99%
“…Sensitive immu-nocytochemical tests have been widely used to identify micrometastasis. These methods can detect 1 cancer cell in 1 x 10 4 to 1 x 10 5 normal cells Wu et al, 2001;Nosotti et al, 2005;Wang et al, 2005;Benlloch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%